Effect of long‐term injection of dopamine on the ovarian growth of Cherax quadricarinatus juvenile females (Parastacidae, Decapoda). (3rd July 2012) - Tropea, Carolina; López Greco, Laura S.
Abstract: The neurotransmitter dopamine (DA) modulates many physiological processes in decapod crustaceans, including reproduction. This study was aimed at evaluating whether the long‐term injection of DA affects ovarian growth in the freshwater crayfish Cherax quadricarinatus . Three experiments were performed with females of different mean initial size: 4.15 g (Group A); 9.65 g (Group B); and 13.98 g (Group C). Treated females were injected with DA and control females with physiological saline twice a week for 90 (Group B), 105 (Group A) and 120 (Group C) days. At the end of the experiments, the animals were killed, and the stage of ovarian development, gonadosomatic index, and mean oocyte diameter were determined. DA had a differential effect according to female size: it negatively affected ovarian growth of females in a weight range of 4–14 g and had no effect on ovarian maturation when injected to females with an initial weight of 14 g. The results are compared with previous reports in freshwater decapod crustaceans.